The effect of die/blank holder and punch radiuses on limit drawing ratio in angular deep-drawing dies - Ozek, Cebeli; Bal, Muhammet (Springer London Ltd, 2009)
Deep-drawing is one of the most important methods used to form sheet metal. The radius of die/blank holder and punch is important for deep-drawing dies because of an effective way to promote deep drawability sheet metal. This paper presents an attempt to determine the effect of various radiuses of die and punch on the limit drawing ratio and was investigated using DIN EN 10130-91 sheet metal. The die/blank holder profile with angles of alpha = 0A degrees, alpha = 2.5A degrees, alpha = 7.5A degrees, alpha = 12.5A degrees, alpha = 15A degrees and die/punch profile with radiuses for R = 10, R = 8, R = 6, R = 4 and R = 0 mm were analyzed to determine the influence of punch force on the limit drawing ratio. The aim of this study is to investigate the effect of radius and angle variables on drawability in the deep-drawing process and to obtain useful data from the industrial field. The experiments show that the limit drawing ratio increased with increasing radius of punch (R), die/blank holder angle (alpha).
Keywords: Deep-drawing; Limit drawing ratio; Blank holder force